Penegakan Hukum Terhadap Pelaku Tindak Pidana Pemerkosaan Berlanjut (Studi Kasus Putusan No: 156/PID.B/2019/PN-TBT) - Ranu Wijaya; Syafruddin Kalo; Mahmud Mulyadi (Iuris Studia: Jurnal Kajian Hukum, 2021)
Judge's Decision Number: 156/Pid.B/2019/PN-TBT, the author feels it is necessary to do research because of the indictment of the Public Prosecutor and the judge's considerations until there is a verdict that decides this case with Articles of continued rape. Formulation of the problem How is the legal regulation of rape in conjunction with Article 64 Paragraph (1) of the Criminal Code, the efforts made by the police and the Public Prosecutor to prove the act of rape by emphasizing Article 64 Paragraph (1) of the Criminal Code, and the judge's considerations in Decision No: 156/Pid .B/2019/PN-TBT. This research is included in normative legal research (normative juridical). This type of research is a case study. The results of the research can be seen, the regulation of the crime of rape is regulated in the Criminal Code, chapter XIV Article 285, while continuing acts are regulated in Article 64 of the Criminal Code, the efforts made by the police and the Public Prosecutor are examining witnesses, requesting a visum et revertum, making indictments, send files to court, hear cases. The judge's legal considerations in this case are not based on law, and the legal discovery by the judge is not in accordance with the legal discovery process. It is recommended that there are special arrangements related to rape in the renewal of criminal law with the latest criminal drafts, the existence of investigators who can prove a criminal act which legally or by law the regulation is not clear in detail, and there is uniformity in the judge's decision